American Embassy, Queen's Park West, Port-of-Spain - Thomas, H.O. (H.O. Thomas, Trinidad, 2009)
Photo of the American Embassy located at Queen's Park West, Port of Spain, Trinidad. The lush green surroundings as well as the American flag are seen in the photo.
Colour: Red, Blue, Green, Brown, Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Embassy buildings--Trinidad and Tobago; 1970